SOSIALISASI PENCEGAHAN TINDAKAN BULLYING DI SEKOLAH DASAR NEGERI 51 SUNGAI RAYA KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - Sulisdiani, Indah; Fatmawati, Fatmawati; Yohanes, Yulius; Marini, Marini; Batualo, Ignasia Debby (Jurnal Abdi Insani, 2024)
Bullying in Indonesia in recent years has shown a significant increase, this is clearly a concern for all parties, especially parents who have children and has become a very unsettling social problem in society. Based on KPAI data, there are 2355 cases of bullying in Indonesia in 2023, 837 of which occurred within the scope of education units. To prevent the spread of bullying within the scope of education units, it is necessary to socialize prevention. The purpose of community service is to provide understanding to students of State Elementary School No. 51 Sungai Raya about bullying, provide education that bullying should not be done, which will have an impact on declining achievement in school and problems in a person’s psyche. The method of implementing PKM is carried out in the form of socialization, lectures and discussions. The results of PKM showed that students understood the material presented, were able to answer the questions asked by the participants, and understood the material well, as evidenced by the posttest score, which reached 76%. Conclusion of this socialization PKM activity can be an alternative to prevent bullying by students. Keywords: Bullying, prevention, socialization